Evaluation of genetic diversity in green gram (Vigna radiata (L.) Wilczek) germplasm for seed yield characters at Prayagraj region - Dip Chaudhary; G. M. Lal (Annals of Agricultural Research, 2024)
Forty-six genotypes of green gram were evaluated to examine genetic diversity and genetic variability. The experiment was conducted in a Randomized Block Design with three replications during the Kharif season 2023. the data were recorded from randomly selected five plants for each genotypes for each replications for fifteen characters. The present investigation, it was concluded that analysis of variance showed significant variation among different genotypes for all characters studied. Pod length, number of secondary branches per plant, number of pods per cluster, harvest index and biological yield all had moderate range of both GCV and PCV in comparison to other characters. In present investigation, moderate GCV coupled with high genetic advance as a percentage of mean, and a high estimate of heritability were found for harvest index, biological yield, and pod length. For the number of primary branches and pods per cluster, moderate heritability with a moderate GCV and moderate genetic advance as a percentage of mean were noted. On the basis of Mahalanobis’ D2 statistics 46 genotypes of green gram were grouped into six clusters. Maximum numbers of 30 genotypes were included in cluster 1 followed by cluster 2 with 8 genotypes, cluster 3 with 5 genotypes, cluster 4, 5 and 6 with only single genotypes in each cluster. It was also reported that the characters like seed yield per plant, biological yield, number of pods per plant, harvest index, seed index, number of pods per cluster, number of clusters per plant, pod length, days to maturity and number of secondary branches contributed about 87.16% towards total divergence alone.